A Naturally Integrated Smart Textile for Wearable Electronics Applications. Issue 1 (22nd November 2019) - Zhao, Jingjing; Fu, Yulin; Xiao, Yuxiang; Dong, Ying; Wang, Xiaohao; Lin, Liwei
Abstract: Smart textiles, which integrate different electronic devices in yarns, fabrics, or garments, have the ability to perceive and respond to environmental stimuli. With the features of mechanical flexibility, knittable integration, and wearable comfort, smart textiles have great potential in wearable electronics. Here, a naturally integrated force sensing textile based on knittable composite coaxial fibers is proposed. A flexible commercial nylon fiber works as a substrate, an evaporated Au layer serves as an inner electrode, and carbon nanotubes and polyaniline act as piezoresistive sensing materials in the coaxial fibers. The assembled sensor retains both high detection performance and outstanding integration properties. A high detection limit, fast response, reversible recovery, mechanical stability, and good repeatability are realized in this sensor. Subsequently, the potential of using a coaxial fiber to achieve naturally knitted structures by an embroidery method is explored. A sensing array can be integrated into designed patterns and can achieve multiple site force measurements. Furthermore, with the flexibility and porosity of textiles, these smart textiles provide breathability in wearable applications, which is valuable in long‐term detection. It is anticipated that the naturally knitted smart textile will be practical in wearable healthcare and long‐term force perception. Abstract : A naturally integrated force sensing textile based on knittable composite coaxial fibers is reported here. Importantly, the smart textile shows excellent sensing properties and presents a flexible, conformal, and breathable integration ability with designed patterns using an embroidery method. With these features, this capability will be useful for long‐term wearable monitoring in healthcare and force perception applications.